Isotopic signals from late Jurassic–early Cretaceous (Volgian–Valanginian) sub-Arctic belemnites, Yatria River, Western Siberia - G.D. Price; J. Mutterlose (Geological Society of London, 2016)
This contribution presents the first detailed oxygen and carbon isotope record from the latest Jurassic–early Cretaceous interval of the Yatria River, subpolar Urals, Siberia. Isotopic compositions have been determined on well-preserved belemnite samples from the genera Lagonibelus , Cylindroteuthis and Acroteuthis . These new data indicate a shift to lower temperatures from the late Volgian into the late Valanginian, with some warmer phases recognized within the Ryazanian and earliest Valanginian. The lowest temperatures of the late Valanginian, consistent with subfreezing polar temperatures, are coincident with an inferred eustatic sea-level fall. A late Valanginian positive shift in carbon isotopes correlates with the carbon isotope excursion recorded from Tethyan successions. The most positive carbon isotope values correspond to the most positive oxygen isotope values (and hence lowest palaeotemperatures). In the absence of widespread Valanginian organic-rich black shale deposition, the carbon isotope excursion may point to increased storage of organic carbon in coastal areas and/or enhanced preservation within stratified waters in high-latitude basins. At these higher latitudes, where rates of weathering were presumably much lower because of the prevalent cold climate, the isotopic data may point to pulses of productivity being brought about by increased riverine nutrient transfer and also by nutrients being released by the melting of ice. The correlation between positive carbon isotopes and cool climates may indicate the effectiveness of these high-latitude carbon sinks and their ability to draw down atmospheric CO 2 , resulting in an ‘inverse greenhouse’ effect.